2009
DOI: 10.1103/physrevc.80.064301
|View full text |Cite
|
Sign up to set email alerts
|

Optimal pair density functional for the description of nuclei with large neutron excess

Abstract: Toward a universal description of pairing properties in nuclei far from stability, we extend the energy density functional by enriching the isovector density dependence in the particle-particle channel (pair density functional, pair-DF). We emphasize the necessity of both the linear and quadratic isovector density terms. The parameters are optimized by the Hartree-Fock-Bogoliubov calculation for 156 nuclei of the mass number A = 118 − 196 and the asymmetry parameter (N − Z)/A < 0.25. We clarify that the pair-D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 60 publications
0
85
0
Order By: Relevance
“…We should note, however, that a densitydependent pairing functional needs to be investigated. Recent work [59] has shown that isovector-density dependence [60] allows a good reproduction of the dependence of pairing gaps on isotope. Such a functional might affect the isotopic dependence of E2 strength as well.…”
Section: B N -And Z-dependencementioning
confidence: 99%
“…We should note, however, that a densitydependent pairing functional needs to be investigated. Recent work [59] has shown that isovector-density dependence [60] allows a good reproduction of the dependence of pairing gaps on isotope. Such a functional might affect the isotopic dependence of E2 strength as well.…”
Section: B N -And Z-dependencementioning
confidence: 99%
“…The starting point of the model is the energy density functional, which we construct from the Skyrme interaction with the parameter set SLy4 [31], and the densitydependent delta interaction (DDDI) adopted as an effective pairing force [13,16,20,[32][33][34][35][36][37][38][39][40][41]. The DDDI is given by…”
Section: Skyrme-hartree-fock-bogoliubov Mean-field Plus Qrpa Apprmentioning
confidence: 99%
“…Our calculations reproduce well the neutron number dependence of experimental data for binding energy, two-neutron separation energy, and odd-even mass staggering of these isotopes with the interaction IS+IV Bare. Recently, the isospin dependent interaction is extended to introduce the quadratic terms of isospin and applied to a wide region of nuclei in the mass table [9]. These results suggest that by introducing the isovector term in the pairing interaction, one can construct a global effective pairing interaction which is applicable to nuclei in a wide range of the nuclear chart.…”
Section: Discussionmentioning
confidence: 99%